(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to identify the contribution of goal orientation to self-regulated learning among high school students in Bungo Regency. This study used quantitative research. The technique used was cluster sampling with a sample of 332 high school students in Bungo Regency. The data collection technique used was a questionnaire, utilizing instruments developed by the researcher based on the dimensions of goal orientation according to Ames (1992) and aspects of self-regulated learning according to Zimmerman (1990). The data analysis technique used was multiple regression analysis, which produced an R2 value of 0.267, showing that goal orientation contributed 26.7% to self-regulated learning among high school students in Bungo Regency. These findings show that goal orientation simultaneously contributes to the self-regulated learning of high school students in Bungo Regency.